Teachers’ Self-Efficacy in Handling Pupils with Emotional Problems: Basis for Teachers’ Training Program - Ma. Gloria E. Liquido; Fritzie B. Mendez (Journal of Interdisciplinary Sciences)
Teachers’ self-efficacy is competence and adaptability in dealing with day-to-day problems of all sorts like stress, physical and mental fatigue, and pressures in school. This study is grounded on Self-Efficacy Theory of Albert Bandura and utilized the questionnaire adapted from Teachers’ Sense of Self-Efficacy Scale of Tschannen-Moran and Woolfolk, Hoy (2001). The same questionnaire was subjected to face and content validation and gained .93 Cronbach Alpha Value or high validity and reliability result. The respondents were 99 public elementary teachers. The results of the study revealed that the majority of the teachers were married, handled large class size or 46 up to 50 pupils in a class, with Teacher 1 position, and have been teaching for about 16-20 years yet claimed to have no in-service training on behavior management. Having found wanting for training on behavior management, teachers turned into their self-efficacy. Their level of self- efficacy was high in aspects of disciplinary self-efficacy, instructional self-efficacy, efficacy to enlist parental involvement, and efficacy to create positive school climate. This is indicative of a high extent of manifestation of abilities of the teachers in the performance of their classroom duties. Same results, though, also indicated that there is a need for development of more effective strategies to deal with pupils with emotional problems and to make the school a “child-friendly” environment. The findings further revealed that the teachers’ experience had significant relationship with their level of disciplinary and instructional self-efficacy, hence the inputs for proposed teachers’ training program.